Vector-boson-induced neutrino mass - Ma, Ernest (2013)
One-loop radiative Majorana neutrino masses through the exchange of scalars have been considered for many years. We show for the first time how such a one-loop mass is also possible through the exchange of vector gauge bosons. It is based on a simple variation of a recently proposed SU(2)N extension of the Standard Model, where a vector boson is a candidate for the dark matter of the Universe.